Consultation with complementary medicine practitioners by individuals with chronic conditions: Characteristics and reasons for consultation in Australian clinical settings. (19th June 2020) - Foley, Hope; Steel, Amie; Adams, Jon
Abstract: The duration and complexity of chronic conditions leads patients to consult complementary medicine (CM) practitioners, yet such care‐seeking by this clinical population has not been thoroughly examined. This study describes characteristics and reasons for consultation amongst those with chronic conditions who consult CM practitioners. A cross‐sectional study surveyed patients in clinics of 39 CM practitioners from the five most accessed CM professions in Australia (chiropractic, massage, osteopathy, acupuncture, naturopathy). Between November 2018 and March 2019, CM practitioners invited 15 consecutive adult patients ( n  = 585 invited) to a self‐administered, hard‐copy survey covering socio‐demographics, chronic condition diagnoses, CM service utilisation and reasons for consulting the CM practitioner. In total, 199 surveys were returned, producing a final sample of n  = 191. Chronic conditions were reported by 153 (80.1%) participants, who were most commonly female (82.4%), aged over 65 years (29.0%), married (55.9%), vocational/trade qualified (40.1%), employed (62.5%), reported financial manageability as not too bad (48.0%), held private health insurance generally (79.0%) and specifically for CM (71.1%). Some socio‐demographic differences were found depending on the profession consulted. Most participants (75.0%) had attended five or more consultations with the CM practitioner. The reasons most commonly given by participants with chronic conditions for consulting the CM practitioner were This healthcare professional is supportive and compassionate ( n  = 136, 97.1%), I believe this type of healthcare is safe ( n  = 131, 95.6%), Improve general wellbeing and prevent future health problems ( n  = 125, 89.3%) and This type of healthcare gives me hope about my future health ( n  = 108, 85.7%). These findings suggest that individuals with chronic conditions may consult CM practitioners to address unmet well‐being or quality of life needs and for compassionate support. The role CM practitioners fill for those with chronic conditions requires further exploration to develop optimal policy and services to manage the growing challenges chronic conditions present to health systems.